Isolation and characterization of Nanocrystalline cellulose based nanobiocomposite from oil palm biomass with potential application in packaging. - KANNA DASAN, YALEENI (2016)
Bionanocomposite is one of the remarkable achievements of nanotechnology in material science to replace conventional non-biodegradable petroleum based plastics for packaging applications. In generaL bionanocomposites are made up of biodegradable polymers (biopolymers) and bio based reinforcing material in the size range of I 0 - I 00 nm in one or more dimensions. Bio based materials could provide a solution for petroleum shortage and waste management problems. One of the potential reinforcing agents is agro industrial biowastcs such as oil palm empty truit bunch tiber "hich has highest composition of cellulose as compared to other fibers. This stud: inwstigate' the effectiveness of nanocrysta\line cellulose (NCC) derived from oil palm empt) fruit bunch (OPEFB) fibers as reinforcement in order to improve the mechanicaL thermaL morphological and barrier properties of bionanocomposite materials. The nanocrystalline cellulose was extracted from oil palm empty fruit bunch fibers through a series of chemical treatment.